Faktor-faktor yang Mempengaruhi Kemauan untuk Membayar Pajak dengan Kesadaran Membayar Pajak sebagai Variabel Intervening - Haedar Haedar; Rismawati Rismawati (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2014)
This research aimed to find factor that affect willingness to pay taxes, case study on individual taxpayers who perform as a freelancer that registered at KPP Pratama Palopo. As these factors are the realization of tax paying knowledge and understanding of taxation laws, and a good perception of the effectiveness of the tax system. This research uses quantitative research methods, where the data obtained from questionnaires. After the data collected by using random sampling , the data was analyzed. Test statistic used is multiple linier regression test, and data obtained were processed using SPSS statistical software.